DESAIN XML SEBAGAI MEKANISME PETUKARAN DATA DALAM HERBARIUM VIRTUAL - Adi wibowo; Muhammad Abdullah (MATEMATIKA, 2011)
The Indonesian Herbaria hold about million records in LIPI and any databases at the universities in the each state and territory. The current system, databases herbarium is applied in the physical collections and there are some computerized databases however usage only in the institution. One of information technology which was applied to support the expansion of virtual herbarium is XML technology for data exchange mechanism in web application. In this article will be studied a design in data exchange mechanism which applied to XML technology for herbarium databases.